Investigating the pitch strength of short pur e-tone pulses in middle frequency range through their chroma recognition by absolute-pitch listeners - Rakowski, Andrzej; Rogowski, Piotr (Interdisciplinary Studies in Musicology, 2018)
A method is proposed for estimating the pitch strength of sounds by measuring the proportion of correct recognitions of their musical pitch (chroma) by expert listeners possessing full absolute pitch. Full absolute pitch (AP) is the ability of some musicians to preserve in their long-term auditory memory the pitch templates of the twelve chromatic tones of the contemporary music system (C, C#, D... etc.) based on the frequency A4 = 440 Hz. This ability is preserved across different octaves in most of the musical pitch scale. Five expert AP listeners, in individual, computer-run sessions, were asked to identify and name the pitch chromas of short tone pulses cut out of twelve sinusoidal vibrations corresponding to the chromatic scale C5 - B5 (523.3 - 987.8 Hz). These tone pulses were composed of n cycles. The value of n was 4, 8, and 16, and so the total number of stimuli investigated was 12 x 3 = 36. All these stimuli were presented in random order to the five AP listeners in a single test, which was run twenty-six times in consecutive sessions (the results of the first session were not used in computations). The results show an increase in correct chroma recognition (and consequently of the pitch strength of a pulse), with n rising from 4 to 16. At n = 4 or 8, the results show also a dependence of chroma recognition on the total pulse duration. Thus, for tone pulses with a low number of cycles (at n=4 and 8), the pitch strength diminishes with increasing pitch and is different in neighbouring parts of a withinoctave musical scale. The discovery of these differences may indicate the relatively high precision of the newly-presented method in estimating the pitch strength of musical sounds.